2011
DOI: 10.1039/c1lc20441f
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable fabrication of micro-structured lab-on-a-chip

Abstract: We have demonstrated a robust platform that can not only sustainably fabricate a lab-on-a-chip (LOC) device using microinjection molding but also elucidate the filling process of microstructures based on the multiscale analysis. In addition, a novel dimensionless number, i.e., the filling number μ(f) which can provide an insight into the underlying filling mechanism for micropillars, has been proposed based on the understanding of the characteristics of polymeric flow and cavity dimension. This study suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Unfortunately, homogeneous mixing of reagents, which is a major limitation of batch reactor system, is impossible to monitor in the inner space of the opaque reactors and it is also difficult for the mass production of reactors 6. To overcome these issues, we presented a microstructure‐embedded cyclic olefin copolymer (COC)‐based microfluidic devices using a microinjection technique, which is highly suitable for the rapid replication and mass production of the microfluidic reactors or devices recently 10. In addition, the COC, which is a class of polymers based on cyclic olefin monomer and ethane, is a highly transparent and the most stable polymer in acid, base, and organic solvents, which are commonly used in the synthesis of various types of nanomaterials 11.…”
Section: Microfluidic Experiments Conditions and Their Fluorescent Promentioning
confidence: 99%
“…Unfortunately, homogeneous mixing of reagents, which is a major limitation of batch reactor system, is impossible to monitor in the inner space of the opaque reactors and it is also difficult for the mass production of reactors 6. To overcome these issues, we presented a microstructure‐embedded cyclic olefin copolymer (COC)‐based microfluidic devices using a microinjection technique, which is highly suitable for the rapid replication and mass production of the microfluidic reactors or devices recently 10. In addition, the COC, which is a class of polymers based on cyclic olefin monomer and ethane, is a highly transparent and the most stable polymer in acid, base, and organic solvents, which are commonly used in the synthesis of various types of nanomaterials 11.…”
Section: Microfluidic Experiments Conditions and Their Fluorescent Promentioning
confidence: 99%
“…Based on these values, the corresponding AR 2 values are calculated, and compared to the maximum ARmax2 values found experimentally (shown in Figure ). Regardless of the geometries, the shapes, the polymers or the conditions used, one can see that for all the products studied, the AR 2 values are quite <95 . Furthermore, from the studies reporting an incomplete filling of the cavities, and giving the results of the final incomplete molding, the values of AR 2 are in the range 20 < AR < 35, corresponding to pressure drops in the range 30 < Δ P (%) < 50% in Figure .…”
Section: Resultsmentioning
confidence: 87%
“…The reliability of the approach proposed in this article is then compared to the experimental findings published in the literature, for the injection molding of polymer parts developed for MEMS devices . The results reported consider that the molding of the micro‐structured parts occurs in similar processing conditions, that is, a mold temperature lower than (i) the glass transition T g for amorphous polymers or (ii) the melting temperature T m for semi‐crystalline polymers.…”
Section: Resultsmentioning
confidence: 88%
“…After location of the master mold in the injection mold machine, COC was injected through the nozzle, and the microfluidic device was released from the mold. The production process and conditions are similar to the previous research which demonstrated various microinjection conditions to form microstructures [17]. Holes of 1 mm in diameter for an inlet and outlet ports were punched to load the sample and buffer solutions into the microchannels.…”
Section: Resultsmentioning
confidence: 99%